Mzeno "Political” (Webster) (International Library of African Music, 2011)
Mzeno (the 'great song', -zena, to play slowly, in a relaxed manner) Mzeno is considered the core movement of the timbila dance. It has a dramatic intensity, with two changes of tempo that makes it unique. When musicians sit around, they often reminisce about Mzeno movements of past years, their music and lyrics. Some mizeno, such as "Hinganyengisa” composed by Katini in 1942 and given below, are widely known among Chopi and recalled for many years. The cycle length is normally 16 beats, the tonality often primarily an alternation of the two chords, CEA and DFB (remembering that these are the Chopi notes, not the Western).
Keywords: African Music